The Lymphocytes Stimulation Induced DNA Release, a Phenomenon Similar to NETosis (2017)
ABSTRACT: The release of DNA into the extracellular milieu by neutrophil during a process called NETosis has been postulated as an additional source of autoantigens; a process believed to be important in the pathogenesis of some autoimmune disease, such as systemic lupus erythematosus (SLE). However, it is not established if the B and T cells undergo the release of DNA to the extracellular milleu, in response to different stimuli. In this study, it was observed that the treatment of B and T cells with PMA, ionomycin and the serum from patients with SLE induced the extracellular DNA presence in B and T cells. These findings suggest that the phenomenon were similar to those observed in neutrophil's Etosis; B and T cells also released their DNA into the extracellular milieu. The findings express that serum from patients with SLE and SLEDAI ≤ 8 triggers the release of extracellular DNA in neutrophils, B and T cells, that suggested the presence of soluble factors in the serum that favoured this phenomenon.